Association Between Complete Edentulism and Comorbidities in Libyan Adults Attending the Removable Prosthodontics Department at the Faculty of Dentistry, University of Benghazi, Libya - Elgtlawi, Mohamed; Fatma Bushaala; Amel Lefsaay (AlQalam Journal of Medical and Applied Sciences, 2025)
Various systemic diseases play an important role in selecting treatment options in dentistry. Almost most of the procedures done in the field of removable prosthodontics need good systemic health or a well-balanced systemic situation. The main objective of this retrospective, cross-sectional study is to investigate the prevalence of systemic disorders among Libyan completely edentulous patients aged 35 years and older attending the removable prosthodontic department at the Faculty of Dentistry, University of Benghazi, Libya. A total of 1317 completely edentulous patients’ case sheets were reviewed, out of which 417 case sheets were chosen. Non-Libyan, healthy patients, patients with major mental retardation, and HIV positive patients were excluded. In our study, it was found that male participants were affected more when compared to females. Patients with diabetes mellitus account for 90.5%, 72.5% accounted for patients with hypertension, 38.5%, 31.5%, and 31.2% accounted for rheumatoid arthritis, cardiovascular problems, and liver diseases, respectively. Out of the included participants, 28% were suffering from cancer, 19.7% accounted for renal problems, and 16.7% accounted for rheumatoid fever; a minority of participants (6.3%) reported having epilepsy. The result of the current study, conducted in a representative sample of Libyan edentulous adults, suggests that an association exists between tooth loss and harmful systemic disorders.